A case of diabetic foot ulcers complicated by severe infection and sepsis with Trueperella bernardiae. Issue 1 (February 2015) - Schneider, Uffe Vest; Ekenberg, Christina; Sode, Nikolaj; Knudsen, Jenny Dahl
Abstract : Introduction: Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) allows us to identify bacteria directly from positive blood cultures with detailed taxonomy naming of the bacterial strains. Knowing the name of the infective bacteria makes it possible to adjust the antibiotic therapy early on. However, it also gives rise to detection of a number of unusual pathogens, which raises new questions on the pathogenicity and medical importance of a number of rarely isolated bacteria such as Trueperella bernardiae . Case presentation: We describe a case of diabetic foot ulcers in a 45‐year‐old male, which led to below‐the‐knee amputation due to widespread infection and sepsis with T. bernardiae and co‐infection with Peptoniphilus lacrimalis . The patient was treated initially with surgical debridement in combination with piperacillin/tazobactam and thereafter with amoxicillin for a total period of 1 month. Conclusion: Based on this case, as well as previous case reports in the literature, we conclude that T. bernardiae is a rarely isolated low‐pathogenic bacterium in patients with severe co‐morbidities. Often co‐infection with other low‐pathogenic bacteria is observed. T. bernardiae is susceptible to and readily treated with β ‐lactam antibiotics.